Male relatedness, lekking behavior patterns, and the potential for kin selection in a Neotropical hummingbird. (12th June 2019) - González, Clementina; Ornelas, Juan Francisco
Abstract: Several models have been proposed to explain the evolution of leks, both in terms of direct or indirect fitness benefits, and in survival. According to kin selection theory, male skewed reproductive success leads unsuccessful males to join successful relatives to increase their inclusive fitness, because their genes would be transmitted indirectly to the next generation. Wedge-tailed Sabrewing ( Campylopterus curvipennis ) is a hummingbird species whose males congregate at leks, in which spatially clustered males sing a particular song with marked differences among neighboring males (song neighborhoods). The maintenance of song neighborhoods presumably depends on juvenile newcomers copying the song type of their neighbors when they establish within a lek, and their acceptance could be more likely if a relative has already settled down in a territory, which in turn could offer fitness benefits explained by kin selection theory. To investigate the potential for kin selection in this species, we genotyped 126 hummingbirds at 10 microsatellite loci and estimated pairwise relatedness among males at 6 leks and in 4 song neighborhoods within 1 focal lek. Within leks, most males were unrelated and only a few were relatives. Moreover, even though relatedness within leks was higher than between leks, it was not higher than 0, which is likely due to isolation by distance. Our results do not support the idea of kin selection as an important force acting on the formation of leks in this species. Additionally, we found no evidence for kin clustering within song neighborhoods, suggesting that juveniles attempting to settle in a lek have to learn the song of the neighborhood (regardless of their kinship) to gain access to territories.